Leveraging Literature for Health Education: The Ideal Teacher Concept in the Works of Khāqānī Shervānī (c. 1120–c. 1199) In Honor of Professor Mohammad Reza Rashed Mohassel's Legacy, Book Chapter Review - Reza Afshari; Seyed Ahmad Emami (Future of Medical Education Journal)
Background: This article explores the integration of Persian poetry, particularly the works of 12th-century poet and physician Khāqānī Shervānī, into modern medical education to enhance communication strategies and patient care.Method: We investigated the potential benefits of using poetry to promote cultural awareness, health literacy, and effective teaching. The research emphasizes the poet's depiction of ideal teaching qualities by analyzing Khaqani's poetry through thematic, linguistic, and educational lenses. Khaqani portrays wisdom, compassion, and authority as essential qualities for educators, drawing on metaphysical, emotional, and symbolic language to highlight the roles of educators and healers in society.Results: The study's results show that Khaqani's metaphors and vivid imagery can inspire medical educators to incorporate humanistic and spiritual elements into their teaching practices. His poetry also reflects a strong awareness of health and medicine, making it a valuable resource for understanding the state of health literacy in 12th-century Persia (Iran). The article argues that incorporating Khaqani's poetry into medical curricula can help improve communication skills, enhance cultural competence, and foster critical thinking in medical students.Conclusion: This approach encourages a more holistic view of education, blending scientific knowledge with cultural and historical perspectives. Ultimately, integrating classical Persian literature into medical education can improve future healthcare professionals' intellectual and emotional development.